2020
DOI: 10.1111/1440-1703.12080
|View full text |Cite
|
Sign up to set email alerts
|

Low‐cost microplastic visualization in feeding experiments using an ultraviolet light‐emitting flashlight

Abstract: Microplastics are pollutants threatening the health of marine, freshwater and terrestrial organisms. To analyze whether an organism is able to ingest microplastics, the organism is usually fed with expensive fluorescent microbeads and placed under a fluorescence microscope for microplastic detection. However, such equipment cannot be afforded by many laboratories. Therefore, we developed a low-cost method to study the ingestion and egestion of low-cost, fluorescent microplastic fragments and fibers by aquatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 32 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…In terms of suitable species, controlled exposure studies specifically examining ingestion and depuration kinetics rarely consider organisms likely exposed to and contaminated with microplastics in the marine environment. For example, ingestion and depuration studies have mainly focused on aquatic invertebrates (Wang X. et al, 2019;Chae and An, 2020;Ehlers et al, 2020), and freshwater fish (Grigorakis et al, 2017;Xiong et al, 2019;Hoang and Felix-Kim, 2020). In contrast, only four ingestion and depuration studies have been conducted on brackish/marine fish (Manabe et al, 2011;Cong et al, 2019;Bour et al, 2020b) despite these being some of the most frequently reported organisms contaminated with microplastics (Lusher, 2015;Kroon F. J. et al, 2018;Jensen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of suitable species, controlled exposure studies specifically examining ingestion and depuration kinetics rarely consider organisms likely exposed to and contaminated with microplastics in the marine environment. For example, ingestion and depuration studies have mainly focused on aquatic invertebrates (Wang X. et al, 2019;Chae and An, 2020;Ehlers et al, 2020), and freshwater fish (Grigorakis et al, 2017;Xiong et al, 2019;Hoang and Felix-Kim, 2020). In contrast, only four ingestion and depuration studies have been conducted on brackish/marine fish (Manabe et al, 2011;Cong et al, 2019;Bour et al, 2020b) despite these being some of the most frequently reported organisms contaminated with microplastics (Lusher, 2015;Kroon F. J. et al, 2018;Jensen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, low-cost and easy detection methods to study the accumulation of microplastics in the environment are available 37 . A tracing method that can be used to visualize fluorescent microplastics using a general industrial ultraviolet flashlight has been reported 38 . However, it can only detect a limited number of microplastic types and cannot be used to identify nonfluorescent microplastics in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…The main challenges to overcome when handling microplastic fibers in the laboratory are exclusion of other airborne fibers, difficulties in weighing and counting the thin and irregular shaped fibers, and production of a homogeneous distribution of fibers in water and other matrices. Only a small number of studies were published so far that conducted exposure experiments with microplastic fibers provided via the diet [6 , 8 , 9 , 11 , 13] . While for gastropods and crustaceans inclusion of fibers in a biofilm or gelatinous matrix is possible, dietary pellets that contain microplastic fibers are more suitable for fish.…”
Section: Methods Detailsmentioning
confidence: 99%